ISOLASI, IDENTIFIKASI DAN UJI ANTIOKSIDAN ASAM FENOLAT DALAM DAUN TEMPUYUNG (Sonchus arvensis L.) DENGAN METODE 1,1-DIFENIL-2-PIKRILHIDRASIL (DPPH) - Yuliarti, Wulan (Chem Info Journal, 2013)
Tempuyung (Sonchus arvensis L.) is widely used for a treatment of asthma, cough and soothe the nerves. Tempuyung leaf contains phenolic acids which exhibit antioxidant activity. This research begins with the preparation of the sample, were making the ethanol extract, isolation (through the stage without hydrolysis (HA), acid hydrolysis (HA) and alkaline hydrolysis (HB)) and identification of phenolic acids and test the antioxidant activity using DPPH method.The results from the isolation of fraction HA, HB and HT were identified using a TLC co-chromatography and quantitative analysis using TLC Scanner, whereas another isolates phenolic acids were identified using UV-Vis, FTIR, and LC –MS spectrophotometer. The result of dentification using a TLC co-chromatography and quantitative analysis using TLC Scanner showed that in fractions of HA, HB and HT is ferulic acid at levels of 4.855%, 4.267% and 8.376%. Based on the identification with UV-Vis, FTIR, and LC-MS spectrophotometer detected that isolate B (from a fraction of HB) is acid p-kumarat. Antioxidant activity assays were performed on extracts of ethanol and isolate B have a value of antioxidant activity (IC50), respectively for 150.860 ppm and 428.718 ppm. this result shows that the antioxidant activity of ethanol extract more greater than isolate B. However, isolates B have a potential to be developed as a source of antioxidant compounds.